Urgensi Pendidikan Agama Islam Dalam Menghadapi Degradasi Moral - Muhammad Ahsan Hidayat; Tegar Syahid Kalijogo Panotogomo; Septi Munawaroh; Sri Handayani; Erin Intan Saputri; Nindi Ayu Apriliana (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Moral degradation is one of the problems that infect almost all levels of society. Data shows that many communities, especially teenagers in Indonesia, are experiencing a decline in morale. Moral values must be owned by every individual because it will determine how someone behaves. Islamic religious education has an important role in human life, because in it is revealed all goodness, noble values, and benefits. This study aims to determine the urgency of Islamic Religious Education in the face of moral degradation. To overcome moral degradation, there needs to be an effort that must be done, one of which is by instilling character education in the family, school, and community as early as possible. This research is qualitative research with literature study methods using sources from journal articles, books, webs, and other relevant sources. The results of this study show that Islamic Religious Education plays an important role in facing the problem of moral degradation, namely: 1) Islamic Religious Education as a strategy to increase the potential for the creation of moral humans, 2) Islamic Religious Education as a revitalization of character education, 3) Islamic Religious Education in forming civil society.